Restructuring the professional organization : accounting, healthcare, and law - Brock, David, 1956- (Routledge, 1999)
In recent years the professions have undergone radical transformation. With the advent of rapidly changing markets, more sophisticated and demanding clients, deregulation and increased competition, the generalist professional partnerships have given way to larger, more corporate forms of organization, comprising increasingly autonomous specialist business units. This volume critically examines these changes through an examination of the archetypes which characterize accounting, health care and law practitioners. With examples drawn from Australia, Canada, the UK and the USA, Restructuri.